If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 4t + -1t Combine like terms: 4t + -1t = 3t 0 = 3t Solving 0 = 3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3t' to each side of the equation. 0 + -3t = 3t + -3t Remove the zero: -3t = 3t + -3t Combine like terms: 3t + -3t = 0 -3t = 0 Divide each side by '-3'. t = 0 Simplifying t = 0
| 4x+2x-3=9y+2y-1 | | 8-32=-8x | | -9=-3/4z | | 100y-8y^2=10y^2 | | 4x+31=11-2x | | 6x-15=-65+x | | -5/8x=-10 | | 3v-18=-3(-v+6) | | x+21=-18 | | 3y-4=3-(-2)y | | 2-3(t-5)=4+1 | | -30n+-30=30 | | 3y-4=3-(-2) | | 5x^2-38x-8=0 | | x^2+4x=4356 | | 45=4x-9 | | 6/5y-8=10 | | 3x-2=5(x-15) | | -10-x/2=7 | | 25v^2z^6-9c^8=0 | | 16y-20y+15y= | | -7x+2(3x-1)=-16-x | | 8n+24=8n+24 | | x^3+2x-10=-22 | | (c-7)(2c+9)= | | x-1.2=2.3 | | 4x+32=12x | | 2.4x-2=0.4(1+6x) | | 3sinx=x-1 | | 6r+3-4r+11=180 | | y=-27-(-34)+(-8)-5 | | y=14-(-9)-25+6 |